Prediction and Measurement of selected Phase Transformation Temperatures of Steels (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
The study deals with precise determination of phase transformation temperatures of steel. A series of experimental measurements were carried out by Differential Thermal Analysis (DTA) and Direct Thermal Analysis (TA) to obtain temperatures very close to the equilibrium temperatures. There are presented results from the high temperatures region, above 1000 °C, with focus on the solidus temperatures (TS), peritectic transition (TP) and liquidus (TL) of multicomponent steels. The data obtained were verified by statistical evaluation and compared with computational thermodynamic and empirical calculations. The calculations were performed using 15 empirical equations obtained by literature research (10 for TL and 5 for TS), as well as by software InterDendritic Solidification (IDS) and Thermo-Calc (2015b, TCFE8; TC). It was verified that both thermo-analytical methods used are set correctly; the results are reproducible, comparable and close to equilibrium state.
Keywords: phase transformation temperatures; InterDendritic Solidification; Thermo-Calc; thermal analysis; steel